Activities of the Iberoamerican Network of Toxicology and Chemical Safety with the Hispanic Organization of Toxicologists - Herrero, Ó.; de la Peña, E. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
This poster shows the close collaboration between the Hispanic Organization of Toxicologists of the Society of Toxicogy (HOT-SOT), with the Ibero-American Network of Toxicology and Chemical Safety (RITSQ). This network was created by the joint initiative of the University of São Paulo, member of IUTOX (Dr. Barros) and the Higher Council for Scientific Research, and the Spanish Association of Toxicology, then its president (Dr. de la Peña). We started activities in 2006 and since then we have held 3 RITSQ meetings, in Montreal, Canada (2007), in Barcelona Spain (2010) and in Mérida, Mexico (2016). In the sixteen years of the existence of the aforementioned RITSQ, we use the web (http://ritsq.org), and where we have presented: news, congresses, courses, news from the festival, and to date we have presented 134 posters, on the website are published by year, all the posters presented in congresses until 2022; The objective of the RITSQ is to publish the information provided to us by e-mail, information on congresses and courses of toxicological interest and chemical safety, publishing all the information on the aforementioned website. In the past year we have communicated the activities held with the Hispanic toxicology organization with which we collaborate and materialize it in this poster number 134. The attached table shows a summary of the published data: news, congresses, courses, network report RITSQ and the number of pages visited, data that has been shown annually since 2018, for this reason we ask potential organizers to kindly provide us with the relevant information about the event and publish it in advance on the web.